Cover Image. (October 2017) - Goodfellow, Bradley W.; Viola, Giulio; Bingen, Bernard; Nuriel, Perach; Kylander‐Clark, Andrew R.C.
Abstract : Estimating the timing of faulting is crucial to modelling tectonics, palaeoseismicity, landscape evolution and fault mechanics. Four slickenfibre calcite samples from a conjugate strike‐slip fault set developed in platformal limestone, SE Sweden, were dated using U–Pb. As illustrated in the figure, these fibres are up to several cm long. Three of the samples yielded an average age of 64.8 ± 6.5 Ma, while the fourth yielded a marginally younger age of 54.7 ± 5.5 Ma. Precipitation of the fibres is interpreted as syndeformational and may reflect far‐field stresses from shortening in the Alps. (See the article by Goodfellow et al., pp.321–328 )